2017
DOI: 10.1002/jor.23534
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical markers of cartilage metabolism are associated with walking biomechanics 6‐months following anterior cruciate ligament reconstruction

Abstract: The purpose of our study was to determine the association between biomechanical outcomes of walking gait (peak vertical ground reaction force [vGRF], vGRF loading rate [vGRF-LR] and knee adduction moment [KAM]) six months following anterior cruciate ligament reconstruction (ACLR) and biochemical markers of serum type-II collagen turnover (collagen type-II cleavage product to collagen type-II C-propeptide [C2C:CPII]), plasma degenerative enzymes (matrix metalloproteinase-3 [MMP-3]), and a pro-inflammatory cytok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
94
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 92 publications
(105 citation statements)
references
References 58 publications
(122 reference statements)
6
94
1
Order By: Relevance
“…(20, 24) Trajectories form the anterior superior iliac spine and sacral cluster markers were low-pass filtered at 10 Hz using a 4th order recurrent Butterworth filter and used to estimate the pelvic center of mass. (26) To more accurately determine habitual walking speed for data analysis, we located the point of initial ground contact for the injured limb striking the force plate during each gait trial and measured the velocity of the pelvis center of mass during a 1-meter distance that began 0.5 meter prior to initial ground contact and ended 0.5 meter after initial ground contact. (20)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(20, 24) Trajectories form the anterior superior iliac spine and sacral cluster markers were low-pass filtered at 10 Hz using a 4th order recurrent Butterworth filter and used to estimate the pelvic center of mass. (26) To more accurately determine habitual walking speed for data analysis, we located the point of initial ground contact for the injured limb striking the force plate during each gait trial and measured the velocity of the pelvis center of mass during a 1-meter distance that began 0.5 meter prior to initial ground contact and ended 0.5 meter after initial ground contact. (20)…”
Section: Methodsmentioning
confidence: 99%
“…During data collection, participants performed 5 gait trials for which they were required to do the following: individually strike an individual force plate with each foot; maintain walking speed within AE5% of the average speed during the practice trials; and not undergo any visible alterations to gait during the trial (e.g., trip or stutter step) (20,24). Trajectories from the anterior superior iliac spine and sacral cluster markers were low-pass filtered at 10 Hz using a fourth-order recurrent Butterworth filter and used to estimate the pelvic center of mass (27). To more accurately determine habitual walking speed for data analysis, we located the point of initial ground contact for the injured extremity striking the force plate during each gait trial and measured the velocity of the pelvis center of mass during a 1-meter distance that began 0.5 meter prior to initial ground contact and ended 0.5 meter after initial ground contact (20).…”
Section: Significance and Innovationsmentioning
confidence: 99%
“…All participants were outfitted with 25 retroreflective markers and a ridged cluster of three additional markers secured over the sacrum . Marker positions were collected using a 10–camera three‐dimensional motion capture system (Vicon Nexus) and post‐processed with Vicon Nexus v1.4.1 motion capture software (Vicon Motion Systems, Oxford, UK).…”
Section: Methodsmentioning
confidence: 99%
“…One potentially modifiable factor that may be related to post‐traumatic OA development is aberrant walking mechanics . Most studies investigating the association between walking mechanics and post‐traumatic OA, however, have examined the tibiofemoral joint, rather than the patellofemoral joint.…”
mentioning
confidence: 99%
“…Most studies investigating the association between walking mechanics and post‐traumatic OA, however, have examined the tibiofemoral joint, rather than the patellofemoral joint. These studies have found that unloading the tibiofemoral joint, especially its medial compartment, early after ACLR is associated with future tibiofemoral OA . One study by Culvenor et al found that those with established, radiographic patellofemoral OA approximately 9 years after ACLR walked with altered mechanics at that time.…”
mentioning
confidence: 99%